2012
DOI: 10.1002/ijc.27690
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear EGFRvIII‐STAT5b complex contributes to glioblastoma cell survival by direct activation of the Bcl‐XL promoter

Abstract: Aberrant EGFR signaling strongly promotes glioma malignancy and treatment resistance. The most prevalent mutation, ΔEGFR/EGFRvIII, is an in-frame deletion of the extracellular domain, which occurs in more than 25% of glioblastomas and enhances growth and survival of tumor cells. Paradoxically, the signaling of the potent oncogene ΔEGFR is of low intensity, raising the question of whether it exhibits preferential signaling to key downstream targets. We have observed levels of phosphorylation of STAT5 at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 47 publications
4
64
0
Order By: Relevance
“…27,51 It has been shown that nuclear EGFRvIII-STAT5B complexes contribute to GBM cell survival by direct activation of the Bcl-XL promoter. 52 However, a link between MET and STAT5B in GBM has not been established before. We show for the first time that STAT5B protein is regulated by MET via miR-134 and that STAT5B mediates the effects of MET and possibly also other RTKs in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…27,51 It has been shown that nuclear EGFRvIII-STAT5B complexes contribute to GBM cell survival by direct activation of the Bcl-XL promoter. 52 However, a link between MET and STAT5B in GBM has not been established before. We show for the first time that STAT5B protein is regulated by MET via miR-134 and that STAT5B mediates the effects of MET and possibly also other RTKs in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…This complex serves as a transcriptional co-activator for a series of tumor-promoting genes such as cyclin D1, iNOS, B-myb, Aurora kinase and Cox-2. 57,70 In this report we evaluated the effect of the JAK/STAT inhibitor, cucurbitacin on malignant human glioma cells in vitro. Application of cucurbitacin to glioma cell lines inhibited cell proliferation and induced cell-cycle arrest regardless of mutational status of p53, PTEN and EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…56 Later, Latha et al demonstrated that EGFRviii cooperated with STAT5 to regulate the Bcl -xL promoter. 57 This prompted us to investigate the role of JAK/STAT inhibitor cucurbitacin-I and the Bcl -2/Bcl -xL antagonist ABT-737 in glioma cell lines. In this study, we report that cotreatment with cucurbitacin-I and ABT-737 induced G2/M arrest and apoptosis regardless of EGFR, PTEN, and TP53 mutation status in malignant human glioma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear localization for ⌬EGFR has been reported recently in the context of association with STAT5 (10) and STAT3 (8,9). These interactions were shown to be important for ⌬EGFR regulation of genes, including the Bcl-XL (10) and Cox2 gene (9). The functional role of the nuclear ⌬EGFR is currently unknown.…”
Section: The Egf Receptor (Egfr)mentioning
confidence: 99%
“…Recent work from several laboratories has indicated that EGFR can shuttle directly into the nucleus in normal proliferating and cancerous cells. The functions of nuclear EGFR include regulating gene transcription via physical interaction with transcription factors (3)(4)(5)(6)(7)(8)(9)(10) and DNA damage repair (11). Correlative studies suggest an association of high nuclear EGFR and poor clinical outcome in breast (12), oral (13,14), bladder (15), and ovarian cancer (12,16), allowing that nuclear EGFR may also be significant in the behavior of gliomas.…”
Section: The Egf Receptor (Egfr)mentioning
confidence: 99%